Local government stewardship for TB elimination in Kerala, India - P S Rakesh; S Nair; R Kamala; MS Manu (Public Health Action, 2023)
The paper documents the role of Local Governance stewardship in the successful implementation of TB elimination activities in Kerala.
Keywords: Strategy, Govt Initiative, Non-communicable Diseases